Wentworth. Season 2 [videorecording (DVD)] - Cormack, Danielle; Da Silva, Nicole; Rabe, Pamela, 1959-; Atkinson, Kate, 1972- (Acorn, 2017)
Drastic changes are in store for the women at Wentworth Prison as the hit Australian drama returns. In Season Two, Bea languishes in solitary, plotting revenge for her daughter's murder, while Franky runs the prison unopposed. But the arrival of sadistic new governor Joan Ferguson threatens Franky's top-dog status. With Franky's contraband operation in her crosshairs, Ferguson attempts to recruit informants, and the inmates are forced to choose a side.